Klotho Protein as a Novel Biomarker for Early Renal Dysfunction in Diabetic Nephropathy - Hind Fawzi Aref (American Journal of Biomedicine and Pharmacy, 2026)
Diabetic nephropathy is one of the most common causes of chronic kidney disease and end-stage renal disease globally and sensitive biomarkers to measure renal injury before irreversible structural damage is evident are needed. There are limitations of traditional biomarkers such as serum creatinine, estimated glomerular filtration rate (eGFR) and albuminuria, as they may only measure late kidney damage rather than early kidney pathology. Recently, Klotho protein emerged as a promising biomarker, which is highly expressed in kidney and has great potential in the diagnosis and treatment of diabetic nephropathy. In addition to being a marker of renal function, Klotho has a critical biological function in phosphate regulation, in modulation of FGF-23 signaling, in reduction of oxidative stress, reduction of inflammatory processes, inhibition of apoptosis, and renal fibrosis. Experimental and clinical data are increasingly accumulating to demonstrate that circulating and urinary Klotho levels are decreased in the early phases of diabetic kidney injury and closely associated with progressive decrease in renal function, increasing albuminuria and progressive eGFR loss. Moreover, the absence of Klotho has been linked with several molecular mechanisms that are essential in the development of diabetic nephropathy, such as transforming growth factor-β, Wnt/β-catenin, nuclear factor-κB, and oxidative stress pathways. The present review summarizes the current knowledge concerning the biology of Klotho, its molecular mechanisms in DKD and its potential as a marker for early renal dysfunction. It also explores the recent clinical data for the diagnostic and prognostic value of Klotho as well as its therapeutic potential. The evidence so far is promising and warrants further prospective clinical use of Klotho as a biomarker for early diagnosis, risk stratification, disease monitoring and personalized care of patients with diabetic nephropathy, but larger prospective studies are needed to confirm this.